Fluoride concentration in public water supply: 72 months of analysis - Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Sumida, Doris Hissako [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2012)
Known as one of the ten most important advances on Public Health in the 20th century, fluoridation of public water supply is a measure of wide population coverage, which is effective on caries control. The city of Araçatuba, in the Northwest region of the São Paulo state, Brazil, started public water supply fluoridation in 1972 and, based on the average annual highest temperature, has kept the fluoride concentration between 0.6 to 0.8 mgF/L. The purpose of this study was to analyze monthly the fluoride concentration in public water supply in the city of Araçatuba during 72 months. Water samples were collected monthly on weekdays, directly from the water distribution network, on pre-established locations and analyzed in duplicate between November 2004 and October 2010 at the Research Laboratory of the Nucleus for Public Health (NEPESCO) of the Public Health Graduate Program from Araçatuba Dental School/UNESP, Brazil, using an fluoride-specific electrode connected to an ion analyzer. From the total of samples (n=591), 67.2% (n=397) presented fluoride concentration between 0.6 and 0.8 mgF/L; 20.6% (n=122) below 0.6 mgF/L; 11.5% (n=68) between 0.8 and 1.2 mgF/L and 0.7% (n=4) above 1.2 mgF/L. Most samples showed fluoride levels within the recommended parameters. Minimal variation was observed among the analyzed collection locations, showing that the city has been able to control the fluoride levels in the public water supply and reinforcing the importance of surveillance and constant monitoring to assure the quality of the water delivered to the population.
Keywords: Fluoridation; Fluoride; Oral health; Water